GENEALOGI GERAKAN PENEGAKAN SYARI’AT ISLAM DI INDONESIA - Sodiqin, Ali (Al-Mazaahib: Jurnal Perbandingan Hukum, 2015)
Enforcement of Islamic law in Indonesia has historically and empirically problem. Debating in this case is not a new discourse of Islamic law, but of a "burden of history" which until this moment has not been completed. Political law of Dutch colonial that twist the facts enactment of Islamic law, caused  marginalization of the Shari'ah in the Indonesian legal system. As a result, there are fragmentation among the Muslims in the form and establishes the basic state at the beginning of independence. Two groups of Muslims appeared, namely the secular nationalist and Islamic nationalist group. During reformation period, appear artifisialistic and reductionist understanding, when Islamic law narrowed at the level of legal provisions that formal and rigid. The emergence of regional regulations of Shari'ah,  was more the efforts of syariah formalization rather than enforcing the doctrine of universal substance. It can be seen from the regulated materials that only at the outside or the skin only, not on the key issues that touch the lives of many people. Besides, it appears a group that understands the shari'ah as a solution and a way of life that is totalistic, without considering aspects of historicity and contextuality. As a result is widespread understanding of Islamism is more emphasis than substance formalization. Transformation understand fundamentalism in the Middle East are sourced from Wahhabi’s teachings that has a big influence in developing the ideology called salafiyah ideological.